Epithelioid Leiomyosarcoma of the Uterus: Modern Outcome-based Appraisal of Diagnostic Criteria in a Large Institutional Series. (20th April 2022) - Chapel, David B.; Nucci, Marisa R.; Quade, Bradley J.; Parra-Herran, Carlos
Abstract : Epithelioid leiomyosarcoma of the uterus is rare and poorly understood. Herein, we characterize a large institutional series of epithelioid leiomyosarcomas aiming to define outcome-determinant diagnostic pathologic features. We also retrieved epithelioid smooth muscle tumors of unknown malignant potential and evaluated a consecutive cohort of leiomyomas for epithelioid subtypes. Of a total of 1177 uterine leiomyosarcomas, 81 (7%) were categorized as epithelioid after review. Epithelioid leiomyosarcoma was strictly defined as having round to polygonal cells with visible pink cytoplasm and round to ovoid nuclei in ≥50% of the tumor volume. Average age was 55 years (range: 26 to 81 y). Median tumor size was 11 cm; tumor was >5 cm in 93% of subjects; 47% were stage 1 at presentation. An infiltrative tumor border was observed, grossly and/or microscopically, in 89% of cases; necrosis was noted in 80%, and vascular invasion in 47%. Mitotic count in 2.4 mm 2 (totalling 10 high-power fields, each field 0.55 mm in diameter) ranged from 3 to 100 (median: 26). All cases had moderate, severe or highly pleomorphic atypia. All cases had 2 or 3 of the following: necrosis, at least moderate atypia and ≥4 mitoses in 2.4 mm 2 . Immunohistochemistry revealed frequent expression of smooth muscle markers including SMA (96%), desmin (95%), and caldesmon (81%). HMB45 and Melan-A were negative in 92% and 100% of cases, respectively. Estrogen and progesterone receptors were expressed by 65% and 54% of tumors, respectively. Follow-up information was available in 68 subjects (median: 23 mo, range: 1 to 254); cancer-related death occurred in 63%, and an additional 15% had recurrent or metastatic disease at last follow-up. Disease-specific survival was shorter in epithelioid leiomyosarcoma patients (median: 44 mo; 35% at 5-y) than in a matched cohort of nonepithelioid leiomyosarcoma (median: 55 mo; 46% at 5-y) ( P =0.03). Three epithelioid smooth muscle tumors of unknown malignant potential were evaluated, all <5 cm in size and with atypia and/or irregular borders but mitotic count below the threshold for malignancy. Two of these had follow-up available, which was uneventful. Of 142 consecutive leiomyomas assessed, none had epithelioid morphology as defined. Epithelioid leiomyosarcoma is an aggressive neoplasm, sometimes with a remarkably low mitotic count. In the setting of an epithelioid smooth muscle tumor of the uterus, we postulate that the diagnosis of malignancy is made in the presence of ≥2 of the following: moderate or severe atypia, ≥4 mitoses/2.4 mm 2 and tumor cell necrosis. In their absence, the finding of tumor size ≥5 cm, vascular invasion, infiltrative edges or atypical mitoses should be treated with caution, and designation as of at least uncertain malignant potential is warranted.